Delay generating factors when requesting medical or nursing treatment by women who have chest pains due to a coronary origin (2010)
Coronary illness constitutes one of the main causes of death among women over 45 years of age. The context in whichsuchillnessarisesamong womenisdeterminedby different factors that constitute a process that generates delays in requesting medical attention and the onset of timely treatment. This descriptive study with a qualitative approach had as objective to identify factors that resulted in delaying request for medical attention among twelve women who had chest pains or symptoms of cardiac ischemic origin, who registered at the Federico Lleras Acosta Hospital and at the clinics Minerva y Medicádiz of the city of Ibagué during the months of August thru November of 2005. The information was gathered via semi structured interviews based on the topic guidelines of the symptom management process; such was then analyzed under the content analysis technique. Delay generating factors when requesting medical treatment by women who have ischemic coronary chest pains in terms of the phases to manage the symptoms are: valuation of the symptom: characteristics of the type of pain, experience with such pain, unprotected by loved ones, a sense of worry for others, disability, fears, underestimating the symptom, attributing the cause; measuring the response capacity: facing the symptom according to beliefs, and selecting the type of assistance: dependent on others and prior experiences with health providers. The factors found are sequential and interrelated. The study identified that factors such as being dependent on others, loved ones not caring and the feeling of not wanting to worry others were definitive in the delay process.